2010
DOI: 10.1158/1055-9965.epi-10-0467
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor H Is Elevated in Bronchoalveolar Lavage Fluid and Sputum from Patients with Lung Cancer

Abstract: Background: Cytologic examination of specimens obtained from the respiratory tract is a lung cancer diagnostic procedure with high specificity but moderate sensitivity. The use of molecular biomarkers may enhance the sensitivity of cytologic examination in the detection of lung cancer.Methods: Complement factor H, a protein secreted by lung cancer cells, was quantified in a series of bronchoalveolar lavage supernatants from lung cancer patients and patients with nonmalignant respiratory diseases. Albumin, tota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…For example, factor H has been shown to be elevated in the bronchoalveolar lavage (BAL) and sputum of lung cancer patients (Pio et al, 2010) and has also been described as a marker for bladder cancer (Cheng et al, 2005). Further studies may shed light on the role of properdin in the pathogenesis of AMD as well as its therapeutic involvement.…”
Section: Resultsmentioning
confidence: 99%
“…For example, factor H has been shown to be elevated in the bronchoalveolar lavage (BAL) and sputum of lung cancer patients (Pio et al, 2010) and has also been described as a marker for bladder cancer (Cheng et al, 2005). Further studies may shed light on the role of properdin in the pathogenesis of AMD as well as its therapeutic involvement.…”
Section: Resultsmentioning
confidence: 99%
“…Pio et al (2010) demonstrated increased levels of complement factor H in sputum of lung cancer patients, and suggested that large plasma proteins as factor H reflects hyperpermeability in tumour circulation. Factor H quantification may aid in improving sensitivity of sputum cytology for lung cancer diagnosis, but is not proof of malignancy similar to hemoptysis.…”
Section: Molecular Analysis Of Sputummentioning
confidence: 98%
“…4 Bronchoscopy can be considered as the primary diagnostic method in patients with suspected pulmonary carcinoma and is also necessary to select the appropriate therapeutic strategy. 5 It is less invasive than other tissue procurement methods, carries a small risk of complications, and has high specificity, although its sensitivity is relatively poor. 5,6 It is expected that approaches that do not require the collection of tumor cells, such as the detection of molecular markers in bronchial fluids, will enhance the sensitivity of cytological examination (30-80% depending on tumor accessibility) 6,7 and improve the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%